Gender Participation and Preference: A Multiple-Case Study on Teaching Circus at PE in Brazilians Schools - Bortoleto, Marco Antonio Coelho; Ontañón Barragán, Teresa; Cardani, Leonora Tanasovici; Funk, Alisan; Melo, Caroline Capellato; Santos Rodrigues, Gilson (Frontiers in Education, 2020)
After more than a decade monitoring physical education instruction in Brazilian elementary schools we noticed an exponential increase in circus activities in both curricular physical education (PE) and in after-school programs. The purpose of this study was to analyze the children’s participation and gender preferences in circus activities, with regard to recent studies reporting substantial gender inequalities in Brazilian PE. Method: A qualitative study, based on multiple-cases design, was conducted in 2 public and 6 private Brazilian elementary schools. Data collection consisted of seventeen semi-structured interviews with PE teachers and school administrators and in situ observations totalizing more than 130 hours. The data were analyzed using Content Analysis (thematic categories). Results: Boys and girls showed high participation levels in both curricular and extracurricular PE circus activities. In grades 1-5, participant activity preference was not linked to gender in either curricular or extracurricular situations and overall physical engagement was high. Gender preferences between activities were identified in grades 6-12: girls for aerial activities (trapeze, silks) and boys for juggling activities. Teacher preferences played an important role in the process of linking activities to specific genders both through modelled behaviour and gendered encouragement of participants. Conclusion: Circus instruction engages children of all genders and is thereby an effective activity to counter low participation in PE for boys and, especially, girls. Although circus activities are not inherently gendered, gender preferences are cultivated by teachers through gendered behaviour modelling (their activity preferences) and encouragement strategies (guiding students to activities based on gender), which is often observed in traditional PE school activities and sports.